Improving Nitrogen Use Efficiency and Yields of Potato through Integrated Use of Nitrogen Fertilizer and Organic Manures under Irrigated Condition in Nepal - Sharma, R; Pande, K R; Upadhyay, K; Gaihre, Y K (SAARC Journal of Agriculture, 2025)
Optimization of nitrogen rate in combination with organic manure could improve nitrogen use efficiency and potato yield. This research was conducted in National Potato Research Program (NPRP), Lalitpur, Nepal for two consecutive years (2022-2023) to determine the optimum combination of N fertilizer across different rates of manures (farmyard manure (FYM) and poultry manure (PM)) to improve yield of potato (cv. Janakdev) under irrigated conditions. Treatments included two factors, where organic manures, both FYM and PM applied at three rates (10, 20 and 30 t/ha) and N applied at three rates (50, 100 and 150 kg/ha). Phosphorus and potassium fertilizers were applied from MOP and DAP as a basal during planting and N was applied from urea in two splits as top and side dressing. Results show that nitrogen and manure had significant interaction effects on tuber yields and nitrogen use efficiency. The highest yield (26.58 t/ha), agronomic efficiency (54.4 kg tuber/kg N) and apparent recovery efficiency of N (50.5%) was obtained from the treatment where FYM and N applied at 30t/ha and 100 Kg N/ha, respectively. Similarly, this treatment also improved soil organic matter. These results suggest that the highest rate of FYM (30t/ha) with 100 kg N/ha could help to achieve higher tuber yield and improve nutrient use efficiencies and soil organic matter. SAARC J. Agric., 23(1): 237-253 (2025)